1998
DOI: 10.1093/jn/128.5.881
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fatty Acid Sources Affect Conjugated Linoleic Acid Concentrations in Milk from Lactating Dairy Cows

Abstract: Conjugated linoleic acid (CLA), a naturally occurring anticarcinogen found in dairy products, is an intermediary product of ruminal biohydrogenation of polyunsaturated fatty acids. Our objective was to determine the effect of different dietary oils, which vary in fatty acid composition, on CLA concentrations in milk from lactating dairy cows. Twelve Holstein cows were randomly assigned to a 3 x 3 Latin square design. Dietary treatments were the addition (53 g/kg dietary dry matter) of peanut oil (high oleic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
171
4
28

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 309 publications
(215 citation statements)
references
References 18 publications
12
171
4
28
Order By: Relevance
“…The SV of the 'linseed 1 vitamin E' diet in Pottier et al (2006) was calculated precisely, the NDF content of the maize silage being available (403 g/kg of DM, unpublished data), and amounted to 1.01/kg of DM, which was very close to the minimum required SV of 1/kg of DM. Here again, we were not able to precisely estimate the SV of the diets in the experiments of Dhiman et al (2000) and Kelly et al (1998). However, we can reasonably assume that the lower dietary NDF contents in the experiments of Dhiman et al (2000) and Kelly et al (1998), as compared to those in the present experiment and in that of Bell et al (2006) (28.30% and 29.10% v. 42.86% and 45.30% of DM, respectively) contributed to lower the SV.…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…The SV of the 'linseed 1 vitamin E' diet in Pottier et al (2006) was calculated precisely, the NDF content of the maize silage being available (403 g/kg of DM, unpublished data), and amounted to 1.01/kg of DM, which was very close to the minimum required SV of 1/kg of DM. Here again, we were not able to precisely estimate the SV of the diets in the experiments of Dhiman et al (2000) and Kelly et al (1998). However, we can reasonably assume that the lower dietary NDF contents in the experiments of Dhiman et al (2000) and Kelly et al (1998), as compared to those in the present experiment and in that of Bell et al (2006) (28.30% and 29.10% v. 42.86% and 45.30% of DM, respectively) contributed to lower the SV.…”
Section: Discussioncontrasting
confidence: 83%
“…Here again, we were not able to precisely estimate the SV of the diets in the experiments of Dhiman et al (2000) and Kelly et al (1998). However, we can reasonably assume that the lower dietary NDF contents in the experiments of Dhiman et al (2000) and Kelly et al (1998), as compared to those in the present experiment and in that of Bell et al (2006) (28.30% and 29.10% v. 42.86% and 45.30% of DM, respectively) contributed to lower the SV. Loor et al (2005) reported a decrease in milk c9,t11-CLA concentration with a 65 : 35 F : C diet compared to a 35 : 65 F : C diet.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…One of the important unsaturated FAs is CLA, C 18:2 ct, which is considered to be anticarcinogenic, antiatherosclerotic and a potent antioxidant component (Kramer et al, 1997;Park et al, 1997;Jensen et al, 1998;Kelly et al, 1998). The presence of CLA in breast-milk reflects the mother's intakes of hydrogenated fat and ruminant products.…”
Section: Discussionmentioning
confidence: 99%